Perception of daylighting in Malaysian mosques by worshippers - Foroughmand, Mostafa (2015)
In the world of mankind, designing buildings is considered as architect’s task, which should be proportional with human factors. Using daylighting appropriately as an architectural elements it can evoke emotions in people and transfer the sense of the place to the users in improving the interior space design. According to contemporary interior design there is a lack of psychological aspect in mosque daylighting, and within this respect, the current research aims to achieve objectives which are trying to develop daylighting in mosque’s prayer hall. This research has been carried out to investigate value and effect of daylighting on people’s perception from. This research also tried to find out the acceptable opening design from the worshippers interest. This study employed quantitative method for data collection. Process of data collection was implicated in four selected mosques with different daylighting by using different instruments to measure variables for determined objectives. Considering objectives of this research, to evaluate daylighting, it was required to measure daylight intensity via lux meter in order to evaluate and compare daylight intensity and daylighting among the selected cases, photographs were used to record the situations of openings and measurable questionnaires based survey was employed to obtain the worshippers emotional and interest from natural lighting during daytime in prayer hall of selected mosques. Findings from this research indicated, daylight intensity can affect the environmental perception of users. In addition it was found that; daylighting can psychologically influence users’ perception from daylighting. The results revealed that, it will be more interesting and acceptable if the daylight float from under the dome and focused in middle of prayer hall and mihrab. It was understand that almost all of respondents preferred openings to be located higher than eye level, on the ceiling and under the dome. Therefore, the recommendations will assist architects to provide effective and sustainable daylighting with broader aspects of human needs in interior design of Malaysian mosques. In fact, this research gathered worshippers’ preferences on daylighting design aspect in prayer hall and significantly provided a recommendation on Malaysian mosque design in future.